Modeling mitigation of influenza epidemics by baloxavir - Zhanwei Du (Nature Portfolio, 2020)
Here, the authors implement a mathematical model that describes how Baloxavir antiviral-induced inhibition of influenza virus replication in infected individuals affects the spread of the virus during epidemics, suggesting that both the scaling up and acceleration of treatment would avert substantial influenza morbidity and mortality every year.